2007
DOI: 10.1038/msb4100188
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐dependent responses of the ErbB signaling network: experimental and modeling analyses

Abstract: Deregulation of ErbB signaling plays a key role in the progression of multiple human cancers. To help understand ErbB signaling quantitatively, in this work we combine traditional experiments with computational modeling, building a model that describes how stimulation of all four ErbB receptors with epidermal growth factor (EGF) and heregulin (HRG) leads to activation of two critical downstream proteins, extracellular-signal-regulated kinase (ERK) and Akt. Model analysis and experimental validation show that (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
252
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(263 citation statements)
references
References 51 publications
(61 reference statements)
5
252
1
1
Order By: Relevance
“…Modelling reveals, however, that negative feedback to receptors can have competing effects, as receptors are responsible for the recruitment of both positive and negative effectors of ERK signaling. 47 Thus, the classification of such feedback as strictly "negative" or "positive" is likely to be context-dependent.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Modelling reveals, however, that negative feedback to receptors can have competing effects, as receptors are responsible for the recruitment of both positive and negative effectors of ERK signaling. 47 Thus, the classification of such feedback as strictly "negative" or "positive" is likely to be context-dependent.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…68 Nevertheless, with ten-fold increases in growth factor dose leading to linear increases in ppERK. 10,47,[60][61][62] One possible explanation for this is variable amplification of the growth factor signal into ppERK signals as a function of growth factor dose. 62 Analysis of a network model for how ErbB receptors lead to activation of ERK through Ras suggested that the control of this variable amplifier strength lies with the amount of active Ras, the Raf-MEK association rate and the MEK dephosphorylation rate.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
See 1 more Smart Citation
“…3C). Parameters for this solution derive from published models of receptor-mediated phosphorylation of the Shc adaptor protein by epidermal growth factor receptor (Birtwistle et al 2007;Chen et al 2009). In this case, separable early/fast and late/slow phase solutions can be defined (Supplemental Eqs.…”
mentioning
confidence: 99%
“…Under the conditions shown in Figure 3C, the With these considerations in mind, we might ask what subset of elementary biochemical reactions in cells are reasonably approximated by Michaelis-Menten kinetics. In the case of the signal transduction networks currently being studied using kinetic modeling, the conclusion appears to be that few if any reactions can be so approximated, even though many can be described quite well by a mass action dynamical system (Chen et al 2000(Chen et al , 2009Birtwistle et al 2007;Albeck et al 2008). The observed mismatch does not involve an absence of well-mixed compartments or the stochastic nature of cellular biochemistry (although both are true), but the very limited range of parameter values over which the MichaelisMenten approximation holds.…”
mentioning
confidence: 99%